PENERAPAN MODEL PEMBELAJARAN ARIAS UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI TEKANAN ZAT KELAS VIII SMP - Novriani, Sri; Azhar, Azhar; Ma`ruf, Zuhdi (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
This research aims to describe the improvement in students' cognitive learning outcomes in substance pressure material through the ARIAS learning model and to determine the differences in students' cognitive learning outcomes through the application of the ARIAS learning model and conventional learning models in substance pressure material. The research method used was a quasi experiment with a posttest-only control design. With data collection techniques in the form of a posttest. The sampling technique in this research used randomization. The sample in this study included classes VIII 1 and VIII 2. The results of descriptive analysis in the experimental class obtained an average cognitive learning outcome of 49.09 which was in the quite good category. Meanwhile, the control class obtained a score of 37.27, which is in the poor category. The hypothesis test result was obtained at 0.001, which means it is smaller than 0.05. There are differences in cognitive learning outcomes that apply the ARIAS learning model and apply conventional learning on substance pressure material in class VIII SMPN 2 Tanah Putih.